2022
DOI: 10.32479/ijeep.12541
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Opportunities of Electricity Generation on Economic Growth in South Africa: An ARDL Approach

Abstract: This study examines the challenges and opportunities of electricity generation from coal on growth of South African economy. The study utilizes the available annual time series data collected from secondary sources (World Bank) spanning for the period from 1971 to 2015. The study employs the Autoregressive Distributed Lag (ARDL) model and an Error Correction Model (ECM) to analyse the challenges and opportunities of coal-fired electricity generation on growth South African economy. Statistical results from rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The empirical model estimation utilised in the study was adopted from the studies of Khobai and Le Roux (2017), Stungwa et al (2022), Hlongwane and Daw (2021a) and Hlongwane and Daw (2021b). The study modifies this model to suit the study's main objective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical model estimation utilised in the study was adopted from the studies of Khobai and Le Roux (2017), Stungwa et al (2022), Hlongwane and Daw (2021a) and Hlongwane and Daw (2021b). The study modifies this model to suit the study's main objective.…”
Section: Methodsmentioning
confidence: 99%
“…The studies that focused on energy consumption and economic growth in South Africa and Zimbabwe were done by Khobai and Le Roux (2017), Stungwa et al (2022), Hlongwane and Daw (2021a), Ouedraogo (2017), Shahbaz et al (2017), Bekun et al, (2019) and Khobai (2018). However, some of the studies did not focus specifically on renewable electricity consumption but they focused on electricity consumption in general.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis by [53] indicates that "real interest rates showed a strong negative long-term correlation but a weakly positive short-term association with economic growth." M2 was shown to have a negative link with the money supply, but M3 showed a positive association over short and long durations.…”
Section: Research Themes a Gross Domestic Productsmentioning
confidence: 99%
“…Besides empirical literature attesting to the positive impact of renewable energy on economic growth, there is a strand of literature that found the consumption of renewable energy to negatively affect economic growth. For example, Hlongwane and Daw (2022), who examined the relationship between renewable electricity consumption for South Africa as well as Zimbabwe using data of time-series nature covering the 1990-2019 period. Using the ARDL-based methodology, the results of the study found renewable energy to negatively affect economic growth in both countries in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of consensus on the subject makes it impossible to predetermine whether the influence of renewable energy use on economic growth in Zimbabwe is positive, negative or neutral -calling for a study on Zimbabwe to unravel the relationship between the two variables in the country. The closest there is, is a study by Hlongwane and Daw (2022). However, the study was narrower in scope as it focused on the impact of renewable electricity consumption on economic growth -…”
Section: Introductionmentioning
confidence: 99%